Regional water data banks project multilateral working group on water resources - Keidar J.; Kawash F. (Food security under water scarcity in the Middle East: Problems and solutions, 2005)
The Regional Water Data Banks Project goal is to enable the exchange of consistent, compatible, and reliable water data and information to support decision making at both local and regional scales. The project consists of a list of recommended activities that were prepared, discussed, and agreed upon by the Core Parties: Israel, Palestine, Jordan. The basic approach adopted for the project is that water data collection and dissemination programs will meet the specific needs of the Core Parties.
LNCV [Landau Network-Centro Volta] International Forum: Food Security under Water Scarcity in the Middle East: Problems and Solutions, 24-27 Nov 2004, Como (Italy)